Quality of marital relationship, partner violence, psychological distress, and resilience in women with primary infertility - Satheesan, Sisira C.; Satyaranayana, Veena A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Primary infertility is an emerging public health problem associated with immense social stigma and adverse mental health consequence. The impact associated with infertility different from culture to culture. There is a paucity of qualitative research in Indian culture. Hence we aimed to explore the quality of marital relationship, psychological distress and resilience in a sample of women with primary infertility. Methods: A cross sectional single group mixed design was used. Sample comprised of 30 adult women, in their late twenties, diagnosed with primary infertility- female factor, by practicing gynaecologist; recruited from a renowned infertility hospital in Bangalore. The participants were assessed on marital quality scale, domestic violence questionnaire, depression anxiety stress scale-21, and Connor Davidson resilience scale after obtaining written informed consent. Data analysis was carried out using descriptive and inferential statistics. Results: Findings indicate high rates of intimate partner violence (47%) in the sample. Poorer quality of marital relationship was associated with higher levels of psychological distress and lower resilience. Women who experienced violence were more likely to report poor quality of marital relationship, higher levels of distress, and lower resilience than women who did not. Experience of at least one form of intimate partner violence emerged as a significant predictor of psychological distress. Conclusions:The need for prevention and intervention service for infertility is at its peak. The findings of the present research have implications in mental health assessment and intervention in this vulnerable group of women.